2020
DOI: 10.1111/bjh.17168
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and myeloma clinical research – experience from the CARDAMON clinical trial

Abstract: and myeloma clinical researchexperience from the CARDAMON clinical trial Fig 1. This flow diagram illustrates the progress through the various phases of the CARDAMON phase II clinical trial, including the impact of COVID-19 on the 70 patients on maintenance K across the two treatment arms at the start of the lockdown period. The 15 patients who stopped K maintenance joined the 170 patients who were already on long-term follow-up on 24 March 2020, bringing the number up to a total of 185. SCT, stem cell transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“… 41 A phase II myeloma RCT found that data collection via telephone and/or video conferencing was valid and complete, with in-person assessments done as needed. 42 In addition, in a RCT assessing the impact of teleintervention on the mental health of adults with type 2 diabetes, telehealth visits helped patients and health professionals maintain relationships and reduced the incidence of diabetes-related emotional distress. 43 Telehealth practices vary across subgroups, however, and may require tailoring.…”
Section: Discussionmentioning
confidence: 99%
“… 41 A phase II myeloma RCT found that data collection via telephone and/or video conferencing was valid and complete, with in-person assessments done as needed. 42 In addition, in a RCT assessing the impact of teleintervention on the mental health of adults with type 2 diabetes, telehealth visits helped patients and health professionals maintain relationships and reduced the incidence of diabetes-related emotional distress. 43 Telehealth practices vary across subgroups, however, and may require tailoring.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has also caused an unprecedented disruption throughout the cancer research community and has slowed down cancer clinical trial operations [ 19 , 20 ]. Once normal service resumes at a population and health-service level, there will be a huge backlog of patients with potential cancer symptoms needing urgent assessment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, after March 25, 2020, delays were permitted up to 14 weeks and when more than 12 months of maintenance had been completed, treatment could stop at the discretion of the investigator. 16 After cases of thrombotic microangiopathy were reported, the protocol was amended to include a step-up carfilzomib dose at the reduced amount of 20 mg/m² for any patient resuming treatment after a break of more than 4 weeks, before returning to the protocol dose of 56 mg/m² (or the last dose amount administered after any reduction).…”
Section: Methodsmentioning
confidence: 99%